2022
DOI: 10.38029/babcockunivmedj.v5i2.143
|View full text |Cite
|
Sign up to set email alerts
|

Baseline anthropometric measurements and Obesity among students in Sagamu, Ogun State, southwest, Nigeria

Abstract: Objectives: This study was designed to determine the anthropometric characteristics and prevalence of obesity among secondary and undergraduate students in Sagamu. Methods: This cross-sectional study involved a selection of 260 students aged 10 to 33 years in Sagamu using a convenience sampling method. The weight, height, and waist and hip circumferences of each subject were measured. The body mass index was then calculated. Data were analyzed using SPSS version 25.0 and p-values< 0.05 were considered stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The body mass index (BMI) result of this research, showed that prevalence of obesity was low among both student groups with 0.5% of secondary school students and 5.2% of university students being classi ed as obese this is similar to ndings from research carried out in Sagamu, Ogun state Nigeria with low prevalence of obesity at 3.1% for secondary school students and 4.6% for undergraduate students classi ed as obese (34). In research carried out on students at the University of Ibadan, contrasting ndings were discovered as the prevalence of obesity was higher, with 7.2% of students classi ed as obese (35), as well as In Onitsha, where the prevalence of obesity among secondary school adolescents was 5.1% (36).…”
Section: Discussionsupporting
confidence: 85%
“…The body mass index (BMI) result of this research, showed that prevalence of obesity was low among both student groups with 0.5% of secondary school students and 5.2% of university students being classi ed as obese this is similar to ndings from research carried out in Sagamu, Ogun state Nigeria with low prevalence of obesity at 3.1% for secondary school students and 4.6% for undergraduate students classi ed as obese (34). In research carried out on students at the University of Ibadan, contrasting ndings were discovered as the prevalence of obesity was higher, with 7.2% of students classi ed as obese (35), as well as In Onitsha, where the prevalence of obesity among secondary school adolescents was 5.1% (36).…”
Section: Discussionsupporting
confidence: 85%
“…Family size: Recoded in to two categories as 1–4, and greater than or equal 5. Body mass index: re-coded in to three categories with values of 0 for underweight 25 kg/m 2 ) 23 . The altitude of the cluster categorized as high and low altitude using 2500 m as reference· Type of place of residence: The variable place of residence recorded as rural and urban in the dataset was used without change.…”
Section: Methodsmentioning
confidence: 99%